Peran Modal Sosial Pada Digitalisasi Perdagangan: Studi Perdagangan Online Pada Mahasiswi FKIP Universitas Sultan Ageng Tirtayasa - Isni Reniati; Agung Fauzi (FKIP, Universitas Palangka Raya, 2022)
The rapid development of information and communication technology has brought major changes to people’s lives and activities, namely the ease of accessing information digitally. Digital transformation of better known as digitalization, comes to bring changes to the way individuals and communities communicate and interact. The arrival of digitalization brings platform new in almost all aspects of everyday human life both in social life, education, health, religion, even economics and business. The level of competition created in terms of business is increasingly challenging for business people such as traders to go throught online (e- commerce). In this study, researchers try to describe and exsplain how the role of sicial capital in the era of trade digitalization the field of food for Students of the Faculty of Teacher Training and Education, Sultan Ageng Tirtayasa University (FKIP UNTIRTA) by involving three elements of social capital in the form of trust, networks, and norms in marketing and business development. The study used a qualitative approach with a descriptive method. This study used data collection teacniques of observation, interviews, and document analysis in the form of previous studies. This study aims to see how the role of social capital in the digitalization of trade in food domain is, then how to starategies of online traders, especially in the food domain, in utilizing digital transformation. The results obtained in the from of (1) the role of social capital in food online trading among Students (FKIP UNTIRTA), (2) the use of digitalization in marketing, (3) the treding system used, (4) and what are the obstacles during carry out trading activities